Comparative Chemical and Quantitative Analysis of Flavonoid Contents In Propolis Samples From South East (Abia) and South West (Ibadan) Of Nigeria - Alaribe , Chinwe S.; Oladipupo , A.R.; Ola, Adisa O.; Okeoma , C.; Adeyeye , A.O.; Basheeru , K. A.; Luca , Rastrelli; Coker , H. A. B. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2018)
Propolis has been used as medicinal agent for centuries. Among the many compounds identified in propolis, flavonoids are considered to be responsible for its main biological activities. Therefore, determination of flavonoids in propolis is a key parameter for evaluation of propolis quality. To continue our research on chemical composition of propolis samples, spectrometric and chromatographic analyses of flavonoid contents collected from two different regions in Nigeria (South East, Abia) and South West, Ibadan) were investigated. Gas chromatography-mass spectrometry technique was used for qualitative analysis. Quantitative flavonoid contents were determined as flavones, flavonols and flavanones expressed as rutin, quercetine and naringenin Equivalent, respectively, using HPLC and UV spectroscopy. Phytochemical screening results of Abia propolis hexane extract (ABPHE), Abia propolis ethanol extract (ABPEE), Ibadan propolis hexane extract (IBPHE), and Ibadan propolis ethanol extract (IBPEE) indicated the presence of flavonoids, alkaloids, steroidal nucleus, saponins, reducing sugars and phenols, while tannins were only detected in ABPEE and IBPEE. The GC-MS analysis identified zingiberene, alpha-farnesene, beta-bisabolene, beta-sesquiphellandrene, phytol and trans-geranylgeraniol in ABPHE and beta-caryophellene, humulene, trans-sesquisabinene hydrate, eremophilene. lauric acid, methyl ester, beta-sesquiphellandrene, lauric acid, ethyl ester, spathulenol, methoxyeugenol, asarone and junipar camphor in IBPHE. The UV/VIS results gave Total Flavonoid Contents (TFCs) for ABPHE (5.59 %) and ABPEE (3.12 %) as 8.70 % whereas TFCs for IBPHE (1.81 %) and IBPEE (12.65 %) as 14.46%. The HPLC results gave TFCs for ABPHE (2.82 %) and ABPEE (3.27 %) as 6.09 % whereas IBPHE (0.37 %) and IBPEE (3.76 %) as 4.13 %. There was no statistically significant difference in the TFCs of the South-east propolis and that of the South-west propolis (p > 0.10) from the two methods.Our findings indicated that despite variability in the concentrations of flavones, flavonols and flavanones contents in the two samples collected from two regions in Nigeria, their total flavonoid contents were comparable to propolis samples collected from China and Rome, Italy. The two propolis samples from South-east and South-west are endowed with flavonoids and can be exploited for pharmaceutical uses.